Evidence of SARS-CoV-2-Specific Memory B Cells Six Months After Vaccination With the BNT162b2 mRNA Vaccine - Ciabattini, Annalisa; Pastore, Gabiria; Fiorino, Fabio; Polvere, Jacopo; Lucchesi, Simone; Pettini, Elena; Auddino, Stefano; Rancan, Ilaria; Durante, Miriam; Miscia, Michele; Rossetti, Barbara; Fabbiani, Massimiliano; et al. (Frontiers in Immunology, 2021)
SARS-CoV-2 mRNA vaccines have demonstrated high efficacy and immunogenicity, but limited information is currently available on memory B cell generation and long-term persistence. Here, we investigated spike-specific memory B cells and humoral responses in 145 subjects, up to 6 months after the BNT162b2 vaccine (Comirnaty) administration. Spike-specific antibodies peaked 7 days after the second dose and significant antibody titers and ACE2/RBD binding inhibiting activity were still observed after 6 months, despite a progressive decline over time. Concomitant to antibody reduction, spike-specific memory B cells, mostly IgG class-switched, increased in the blood of vaccinees and persisted 6 months after vaccination. Following the in vitro restimulation, circulating memory B cells reactivated and produced spike-specific antibodies. A high frequency of spike-specific IgG+ plasmablasts, identified by computational analysis 7 days after boost, positively correlated with the generation of IgG+ memory B cells at 6 months. These data demonstrate that mRNA BNT162b2 vaccine elicits strong B cell immunity with spike-specific memory B cells that still persist 6 months after vaccination, playing a crucial role for a rapid response to SARS-CoV-2 virus encounter.